'For All the Fanatics of Drama Out There - This is Your Book!' An Analysis of Student Podcast Compositions for Responding to Literary Texts. Issue 1 (2nd January 2023) - O'Grady, Rhiannon Julia; Cassany, Daniel; Knight, Janine
ABSTRACT: This article is an exploration of two podcast composition projects carried out in English literature classes at a private, not for profit secondary school in Catalunya. Despite a growing body of research that indicates the richness of meaning making offered by multimodality, written texts remain central in many formal educational settings. Factors of traditionality, time constraints, and exam pressures, often lead educators to overlook the possibilities offered by digital audio production. Using an approach that analyses pupils' composition processes and outcomes, we demonstrate some of the affordances that can be identified when multimodal project work is offered as a way for students to respond to literature. The results indicate that podcast compositions can form part of a student-focused model that enhances pupils' confidence through collaborative discussion, supporting them to show agency by drawing on their own cultural references to produce new spoken texts for an intended audience.